Analisis Pengelolaan Keuangan pada Usaha Mikro Kecil dan Menengah Nasi Babi Kereta Senja di Kota Kupang - Amelia Monica Stilly Amalo; Lustry Rahayu; Emilia Gie; Arjuna Purba (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This research aims to analyze the issues in financial management of the micro, small and medium Kereta Senja in Kupang City. The background of this research is based on the weak financial management system that has the potential to cause business losses. The research method used is a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. To identify the root causes of the problems, a Fishbone analysis with a 5M approach (Man, Method, Machine, Material, Measurement) was used. The research results show that the low awareness of business actors regarding the importance of financial management is the main factor behind the weak financial system of MSMEs, the absence of SOP’s, limited use of technology, and financial evaluations based solely on intuition. Therefore, it is necessary to enhance the capacity of business actors through basic training, the formulation of SOPs, and the implementation of a structured and consistent financial recording system to support more effective and sustainable financial management